Upaya Peningkatan Kesehatan Edukasi Kesiapan Warga dalam Menghadapi Bencana Fase Impact di Desa Wonorejo Karanganyar - Ika Subekti Wulandari; Maria Wisnu Kanita (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Indonesia is included in the list of countries most at risk of disaster. So that disaster preparedness is needed which is an effort to prevent the onset of crisis due to disaster which is focused on developing plans to deal with disasters. The problem that arises is that there are still many Indonesian citizens who do not know and understand what a disaster is, how to anticipate and overcome a disaster. The purpose of this community service is to increase community preparedness in the face of the impact phase of disaster in the village of Karanganyar Wonorejo. Methods: The design of this study was a quasi-experiment with a pre-post without control group design involving 29 respondents. Result: The results of education on the readiness of residents in facing the impact phase of the disaster proved to significantly increase knowledge with a p-value of 0.006. Conclusion: Increasing the readiness of citizens in facing disasters in the impact phase can be done by providing massive education and information to the community